Decision Support System For Computer Recommendations Using Web-Based Fuzzy Tahani Logic Method - Farrell Ega Santoso; Ika Ratna Indra Astutik (Procedia of Engineering and Life Science, 2021)
Nowadays people are familiar with computers and many use computers to support their needs, but many people do not understand the specifications of computers that suit their needs, so a web-based application is made that provides recommendations for computer specifications using fuzzy logic. This research method uses observation to obtain information about computer components. The results of this study indicate the recommendations for computer components, namely computer, monitors, keyboard, and mouse according to the user's wishes. The conclusion of this study, this website makes it easier for users to choose computer components.